Fostering EFL Junior Highschool Students’ Speaking Skill Through Vlogging Strategy (Tamaddun, 2023)
In an era marked by technological advancements and a burgeoning digital landscape, the realm of education has witnessed a paradigm shift, particularly in language acquisition. This research embarks on an innovative exploration of the efficacy of vlogging as a pedagogical strategy to enhance the speaking skills of Eighth Grade English as a Foreign Language (EFL) students. This research was mainly conducted in order to prove that Vlogging Strategy could improve speaking skill of the eight grade students of SMP Santo Thomas 3 Medan in the Academic Year of 2022/2023 The study employs a classroom action research (CAR) approach, encompassing quantitative analysis of pre-test, formative tests, and post-test scores, complemented by questionnaire insights gleaned from student feedback and reflections. The data analysis showed the mean score increased from 58,8 in Pre-test with 20% of the students got score ≥ 75, in Formative-test 70,56 with 40% of the students got score ≥ 75, and 77,08 in Post-test with 76% of the students got score ≥ 75. The findings underscore the transformative potential of vlogging in the EFL classroom. Quantitative analysis reveals a statistically significant improvement in students' speaking skills, accentuating the effectiveness of vlogging as a language learning tool. This research not only contributes to the existing literature on technology-enhanced language education but also pioneers the exploration of vlogging as a specific and innovative approach within the EFL context. Beyond statistical validation, the study delves into the practical implications for educators, advocating for a shift towards interactive, student-centric pedagogical approaches. It sheds light on heightened student engagement and motivation, showcasing vlogging's capacity to nurture creativity and authentic language practice. This research reinforces the broader narrative of technology's indispensable role in language education and underscores the contemporary necessity of digital literacy alongside traditional language skills.